2022
DOI: 10.3390/genes13081493
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alkaline Salt Tolerance Genes in Brassica napus L. by Transcriptome Analysis

Abstract: Soil salt alkalization is one major abiotic factor reducing the productivity of crops, including rapeseed, an indispensable oil crop and vegetable. The mechanism studies of alkali salt tolerance can help breed highly resistant varieties. In the current study, rapeseed (B. napus) line 2205 exhibited more tolerance to alkaline salt than line 1423 did. In line 2205, the lesser plasma membrane damage index, the accumulated osmotic solute, and higher antioxidant enzyme activities contributed to alkaline tolerance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Currently, various omics techniques have become an effective strategy to better understand the response mechanisms to environmental stresses such as salt stress ( Dai et al., 2022 ). In recent years, there have been many reports on the study of salt tolerance in plants through transcriptomic approaches ( Chen et al., 2022a ; Ge et al., 2022 ; Wang et al., 2022a ; Xu et al., 2022 ). Recently, metabolomic studies on salt tolerance in plants have reported that increased accumulation of metabolites and related pathways that mainly regulate the antioxidant defense system in different Indian mustard ( Brassica juncea ) varieties under different periods of salt stress give the high-yielding variety CS60 an advantage over CS245-2-80-7 and may be the main tolerance mechanism for its resistance to salt stress ( Singh et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, various omics techniques have become an effective strategy to better understand the response mechanisms to environmental stresses such as salt stress ( Dai et al., 2022 ). In recent years, there have been many reports on the study of salt tolerance in plants through transcriptomic approaches ( Chen et al., 2022a ; Ge et al., 2022 ; Wang et al., 2022a ; Xu et al., 2022 ). Recently, metabolomic studies on salt tolerance in plants have reported that increased accumulation of metabolites and related pathways that mainly regulate the antioxidant defense system in different Indian mustard ( Brassica juncea ) varieties under different periods of salt stress give the high-yielding variety CS60 an advantage over CS245-2-80-7 and may be the main tolerance mechanism for its resistance to salt stress ( Singh et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A transcriptomics analysis played a role in revealing the alkalinity adaptation strategies of lentils and in identifying the significantly upregulated differently expressed genes (DEGs) involved in abscisic acid (ABA) signaling and secondary metabolite synthesis [ 24 ]. Xu et al [ 25 ] identified 12 cross-differentially expressed genes in response to the alkali stress of rapeseed; the major genes that responded specifically in tolerant material were mainly enriched in carbohydrate metabolism, photosynthetic processes, ROS regulation, and the response to salt stress. In recent years, the combination of the GWAS and RNA-seq has proven to be reliable for identifying potential genes related to abiotic stress.…”
Section: Introductionmentioning
confidence: 99%